Error In Translating Indonesian Noun Phrases Into English Made By Second Semester Students Of English Education Department In Muhammadiyah University Of Surakarta 2014/2015 Academic Year - Kurniawati, Titik; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Anam Sutopo, M.Hum (2015)
The objectives of this study are clasify the types of errors, to identify the frequency of errors, and to explain the sources of errors made by students in their translating Indonesian noun phrases made by second semester students of English Education Department in Muhammadiyah University of Surakarta 2014/2015 Academic Year. This research is descriptive qualitative research. The methods of collecting data are observation, interviewing, and document collection and elicitation method. In techniques for analyzing data are identifying the errors from the students' answer sheet, classifying errors, describing errors based on their type, analyzing the students' errors, and drawing conclusion. The results of the analysis show that second semester students of English Education Department in Muhammadiyah University of Surakarta 2014/2015 Academic Year still make 326 errors in their composition. She finds that from 746 data, there are two classifications of error based on the combination of linguistic category and surface strategy taxonomy. They are lexicals error consists of 64 errors. The errors classified into three errors, there are misselection 14, 92%, the use of indonesian words 2, 45%, and wrong spelling 2, 14%. The second is grammar error consists of 262 errors. The error classified into six errors, they are missordering 20, 85%, combination of V1+N instead of V ing + noun 9,5%, combination of N+N instead of N+Ving 14,41%, combination of N+N instead of V3+N 11,96%, combination of N+N instead of N+V3 13, 80%, and combination of N+N instead of N+preposition+N 9, 81%.